Making Debt Work For Development and Macroeconomic Stability. (Policy Papers; Policy Paper, 2022)
The coronavirus crisis has stiffened debt and development-related headwinds that had become strong even before 2020. Sustaining development while maintaining debt sustainability has been made harder by the protracted effects of the pandemic on public finances, earnings and employment, and human capital accumulation of vulnerable populations. The fiscal support programs financed by public debt provided relief and saved lives and livelihoods. But debt-induced uncertainty can now dampen investment and growth, especially given rising global interest rates. Bigger debt servicing burdens will reduce available fiscal space for development and stabilization and growing sovereign debt financing needs can crowd out domestic investment. Over-indebtedness can adversely affect economic development through many channels-"debt overhang," "fiscal space," "crowding out" and increased crisis risk -making countries vulnerable to abrupt changes in market sentiment, jeopardizing both stability and growth.